The Dynamics of Religious Practice in Spain from the Mid-19th Century to 2010 - Rossi, Maurizio (Journal for the scientific study of religion, 2016)
Like other Western countries, Spain is rapidly becoming more secularized. While there is almost unanimous agreement that this is happening, significant discord exists about the phases of the process and the speed of its development. This is mostly due to the use of partial and sometimes unreliable data. The aim of this study is to remedy these uncertainties. Our work is based on the data provided by time-use surveys conducted in 2003 and 2010. Using some basic provisional but reasonable assumptions, we demonstrate that it is possible to identify a plausible dynamic of secularization in Spain starting in the second half of the 19th century. We also highlight the fact that the different indicators feature some significant time lags. Indeed, the dating of the start of the secularization process varies depending on whether reference is made to data on birth cohorts, the overall population, or the visibility of the phenomenon.